Excellence in library services - Syed Azamthullah, Syed Salim Agha (IIUM Press, 2009)
Introduction : As a "doorway to a lifetime of learning" the library is the heart of the university community. The social responsibility and dynamic role of the library as a critical community service go beyond just providing access to information. It "maximizes the utilization of bibliographic records for the benefit of society'; serves as a mediator between man and graphic and/or digital records; tames the "chaotic world of information"; organizes and preserves "the written record of civilization"; provides service with a high sense of purpose and dedication; is an agency of communication that enables the transfer of information; holds within its midst 'knowledge needed to craft a creative solution to any problem'; prevents societies from "reinventing the wheel"; is a well organized joy where people go "to seek sanctuary and quiet"; enables browsing and serendipitous learning, and above alt is the "oldest continuing institution in existence," The establishment of the nUM library in 1983 and the investment in it ever since was and has always been viewed as a strategic investment in the University's future.